Lnvestigations on effects of various biochemical parameters in blood and cerebrospinal fluid of some tranquilizers in dogs - Celal İZCİ; Nuri YAVRU; Ali Muhtar TİFTİK; Yılmaz KOÇ (Eurasian Journal of Veterinary Sciences)
This study was carried out in three groups, that each group consists of 5 dogs. In the first group xylazine, in the second group propionylprozmazine and third group promazine was used intravenously, as a doses of mg per kg body weight 3.5, 0.3 and 3 mg respectively. In all the animals blood an cerebrospinal fluid samples were taken first before and then after the application of drug on 30th, 60th and 120th minutes. In the samples changes in glucose, sodium, potassium, calcium and phosphor paramaters were investigated.